The Impact Of Transformational Leadership On Energy Innovation: A Review From The Viewpoint Of The Consumer - Saefullah, Aep; Hidayatullah, Syarif; Fadli, Ahmad; Candra, Hendra (Universitas Dharma Wacana, 2024)
In the contemporary era, the topic of energy innovation is gaining significant importance. Consumers, as end-users of energy, play a crucial role in propelling advancements in this field. This study investigates the impact of transformational leadership on energy innovation from the perspective of consumers. The primary objective is to ascertain how transformational leadership influences energy innovation as perceived by consumers. Employing a descriptive qualitative methodology, this research focuses on five consumers representing the general public of energy users. Data were collected through literature reviews, interviews, and observations conducted over a two-month period from March to April 2024. The findings indicate that consumers highly value energy innovation, particularly regarding its efficiency, sustainability, and environmental impact. These insights reveal that sustainability not only shapes product perceptions but also drives purchasing decisions and enhances consumer loyalty. Sustainability has become a pivotal factor in consumer buying choices, influencing their perception of value and satisfaction with products. Furthermore, by integrating technological innovation with ethical practices and transparent, effective sustainability policies, companies can secure long-term trust and support from their customers. This research provides critical insights into the intersection of transformational leadership and energy innovation from a consumer standpoint. It offers valuable implications for governments and corporations in formulating strategies that promote sustainable energy innovation. Ultimately, this study aims to contribute to the advancement of energy innovation by encouraging leadership practices that align with consumer expectations for sustainability, ethical business operations, and transparency